Crystal structure of 1,4-bis(methylpyridinium benzene) bis(1,2-dicyanoethene-1,2-dithiolato-κ2S:S)nickel(II), C26H18N6NiS4 - Yan Wei-Hong; Pan Hui-Yan (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C26H18N6NiS4, triclinic, P1¯$\overline{1}$ (no. 2), a = 8.2947(4) Å, b = 8.9964(5) Å, c = 9.4210(5) Å, α = 70.988(1)°, β = 79.971(1)°, γ = 82.567(1)°, V = 652.52(6) Å3, Z = 1, Rgt(F) = 0.0340, wRref(F2) = 0.0643, T = 296(2) K.